PENGEMBANGAN MEDIA PEMBELAJARAN KOTAK GAMBAR KATA (KOGATA) UNTUK MENINGKATKAN KETERAMPILAN MENULIS KALIMAT SEDERHANA SISWA KELAS III SDN DUKUH 01 JAKARTA TIMUR - Sulistyani Puteri Ramadhani; Safa Nabila Aulia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop the Word Picture Box (KOGATA) learning media for teaching simple sentence construction based on Subject, Predicate, Object, and Adverb (SPOK) elements to third-grade elementary school students and to determine its feasibility and effectiveness. This research employed the Research and Development (R&D) method using the Dick and Carey development model, which consists of identifying instructional goals, conducting instructional and learner analyses, formulating learning objectives, developing assessment instruments, designing instructional strategies, developing instructional media, expert validation, product revision, small-group trials, and large-group trials. The validation results indicated that KOGATA obtained feasibility percentages of 97% from media experts, 100% from material experts, and 94% from language experts, indicating that the media is highly feasible for classroom implementation. The small-group trial showed an increase in the average score from 73.33 to 84.33, with an N-Gain score of 0.41 (moderate category). Meanwhile, the large-group trial showed an increase in the average score from 79.29 to 89.33, with an N-Gain score of 0.49 (moderate category). These findings indicate that the KOGATA learning media effectively improves students' ability to construct simple sentences based on SPOK elements while creating a more active, engaging, and enjoyable learning environment.